Model Formula Model Formula Altman Z Score Dalam Memprediksi dan Menilai Kinerja KeuanganAltman Z Score Dalam Memprediksi Dan Menilai Kinerja Keuangan - Wibowo, Doni Teguh; Hidayah, Nurul (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Formula Altman Z-score, uses various ratios that create a predictor of difficulty. Characteristics of these ratios are used to identify possible future profit difficulties. Financial ratios used in this method are WCTA, RETA, EBITTA, MVEBVL, and STA. Problem in this research lies in two dimensions, first dimension is how to evaluate company's financial performance using the components of financial ratios used in the Altman model, and second dimension is how the Altman Z-score formula predicts the financial difficulties of companies a potential bankruptcy. This study aims to determine the accuracy of the Altman Z-score formula in predicting the financial difficulties of non-cyclical consumer sector on the Indonesia Stock Exchange in the 2018-2021. The research results based on five financial ratios in the Altman equation formula base on observation period CAMP and ADES companies are predicted to be in the healthy financial category, and ULTJ, MYOR, AISA, CLEO, ICBP companies are in the dangerous zone, and FOOD, INDF, ALTO companies are in the bankruptcy predicted and potential bankruptcy in the future.